Advances in Polymer Based Microwave Absorbers: From Design Principles to Technological Breakthroughs - Ray S.; Panwar R. (My University, 2025)
Designing effective microwave-absorbing materials (MAMs) and microwave-absorbing structures (MASs) can be complex and requires a deep understanding of microwave absorption theory, material science, and engineering principles. This review article offers an extensive overview of polymer-constituted MAMs and MASs, highlighting their significance in modern electromagnetic interference (EMI) mitigation and stealth applications. Polymer-based MAMs have gained significant attention due to their tunable electromagnetic (EM) properties, lightweight nature, flexibility, and versatility in design. This paper dives into the synthesis methods, material properties, and various underlying EM mechanisms that govern the absorption behavior of these polymers in different frequency ranges. This article surveys various polymer-based systems such as intrinsically conducting polymers (ICPs), polymer nanocomposites, metamaterials (MMs), and frequency selective surfaces (FSSs) elucidating their unique features in microwave absorption applications. It explores the critical factors influencing absorption performance, including dielectric and magnetic properties, filler content, morphology, and thickness. Additionally, the article addresses the challenges associated with achieving broadband absorption with a lightweight and conformal structure. The comprehensive survey of recent research contributions and technological advancements demonstrates the potential applications of polymer-constituted microwave absorbers in diverse fields. It also discusses developing novel fabrication and performance evaluation techniques for polymer-constituted absorbers. In summary, this article is useful for researchers in designing and optimizing polymer-based MAMs and MASs. IEEE